Response of KDML105 and RD41 rice varieties grown on a Typic Natrustalf to granulated pig manure and chemical fertilizers - Rann, Vannak; Anusontpornperm, Somchai; Thanachit, Suphicha; Sreewongchai, Tanee (Agriculture and Natural Resources, 2016)
A study on the effect of composted pig manure and chemical fertilizers on the yield and plant nutrients uptake of the KDML105 and RD41 rice varieties grown on a Typic Natrustalf was carried out in a field of the Farmer Occupational Research and Development Centre, Ban Panead, Khok Samrong district, Lopburi province in 2013. The soil on the experimental area contained some soil constraints that adversely gave a low rice yield; therefore, the study investigated the response of two rice varieties to the application of composted pig manure and chemical fertilizers. A factorial, randomized, complete block design with three replications was employed. The first factor comprised the two rice varieties while the second factor consisted of six treatments consisting of no added fertilizer, sole and a combination of composted pig manure and chemical fertilizers. The results showed that both rice varieties produced similar amounts of grain yieldd1.32 t/ha for the KDML105 variety and 1.28 t/ha for the RD41 variety. The KDML105 variety had greater vegetative growth than the RD41 variety. The application of 50% composted pig manure plus 100% chemical fertilizers highly significantly promoted the rice grain yield to the highest level achieved (1.88 t/ha), whereas the sole application of chemical fertilizer (T2) as commonly used by local farmers and 50% composted pig manure (T4) gave much lower yields, albeit greater than the control without manure added or fertilization. Almost all major and minor plant nutrients were statistically more concentrated in the grain of RD41 than in KDML105, while some micronutrients accumulated more in KDML105. In general, the application of 50% composted pig manure together with 100% chemical fertilizer (T5) effectively promoted the highest uptake of most plant nutrients in both the grain and straw, which coincided with the highest grain yield. While there were no statistically significant differences, RD41 with the addition of 50% composted pig manure together with 100% chemical fertilizer tended to give the highest grain yield of 2.29 t/ha when grown on this poor soil.